A novel familial case of diffuse leukodystrophy related to NDUFV1 compound heterozygous mutations (2013)
NDUFV1 mutations have been related to encephalopathic phenotypes due to mitochondrial energy metabolism disturbances. In this study, we report two siblings affected by a diffuse leukodystrophy, who carry the NDUFV1 c.1156C>T (p.Arg386Cys) missense mutation and a novel 42-bp deletion. Bioinformatic and molecular analysis indicated that this deletion lead to the synthesis of mRNA molecules carrying a premature stop codon, which might be degraded by the nonsense-mediated decay system. Our results add information on the molecular basis and the phenotypic features of mitochondrial disease caused by NDUFV1 mutations. © 2013 Elsevier B.V. and Mitochondria Research Society. All rights reserved.